2020
DOI: 10.1182/bloodadvances.2019000921
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of factors IX and XI in murine placenta and hemostasis under conditions of low tissue factor

Abstract: The intrinsic tenase complex (FIXa-FVIIIa) of the intrinsic coagulation pathway and, to a lesser extent, thrombin-mediated activation of FXI, are necessary to amplify tissue factor (TF)-FVIIa–initiated thrombin generation. In this study, we determined the contribution of murine FIX and FXI to TF-dependent thrombin generation in vitro. We further investigated TF-dependent FIX activation in mice and the contribution of this pathway to hemostasis. Thrombin generation was decreased in FIX- but not in FXI-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 54 publications
4
19
0
Order By: Relevance
“…20 These low TF mice survive to wean at close to the expected frequency but exhibit spontaneous fatal hemorrhages later in life. 21,22 Low TF mice demonstrate a mildly prolonged bleeding in the tail transection and saphenous laser injury models. 23,24 It is notable that mice expressing very low levels of FVII have a similar phenotype to low TF mice.…”
Section: How Can Patients With Tf Deficiency Be Identified In the Futmentioning
confidence: 97%
See 1 more Smart Citation
“…20 These low TF mice survive to wean at close to the expected frequency but exhibit spontaneous fatal hemorrhages later in life. 21,22 Low TF mice demonstrate a mildly prolonged bleeding in the tail transection and saphenous laser injury models. 23,24 It is notable that mice expressing very low levels of FVII have a similar phenotype to low TF mice.…”
Section: How Can Patients With Tf Deficiency Be Identified In the Futmentioning
confidence: 97%
“…Importantly, TF‐null mice can be rescued by the expression of a low level (~1%) of human TF from a human TF minigene 20 . These low TF mice survive to wean at close to the expected frequency but exhibit spontaneous fatal hemorrhages later in life 21,22 . Low TF mice demonstrate a mildly prolonged bleeding in the tail transection and saphenous laser injury models 23,24 .…”
Section: Factor Gene Disease Estimated Frequency Gnomad Plof Frequenmentioning
confidence: 99%
“…70 Interestingly, a recent study showed that FXI, but not FIX deficiency in mice with low levels of TF is associated with increased blood pool size in the placenta, suggesting a tissue-specific role for FXI in mice. 71 Postnatal survival of low TF mice was however dependent on FIX levels. 71 Similar antithrombotic effects of FXI deficiency could be shown in a FeCl 3 -induced vena cava thrombosis mouse model.…”
Section: Animal Models To Study Thrombosis and Bleedingmentioning
confidence: 99%
“…71 Postnatal survival of low TF mice was however dependent on FIX levels. 71 Similar antithrombotic effects of FXI deficiency could be shown in a FeCl 3 -induced vena cava thrombosis mouse model. 72 Likewise, the role of FXI in development of thrombosis has been studied in higher species.…”
Section: Animal Models To Study Thrombosis and Bleedingmentioning
confidence: 99%
“…70 Interestingly, a recent study showed that FXI, but not FIX deficiency in mice with low levels of TF is associated with increased blood pool size in the placenta, suggesting a tissue-specific role for FXI in mice. 71 Postnatal survival of low TF mice was however dependent on FIX levels. 71 Similar antithrombotic effects of FXI deficiency could be shown in a FeCl3-induced vena cava thrombosis mouse model.…”
Section: Animal Models To Study Thrombosis and Bleedingmentioning
confidence: 99%